Vascular Endothelial Growth Factor B and Its Signaling - Lal, Nathaniel; Puri, Karanjit; Rodrigues, Brian (Frontiers in Cardiovascular Medicine, 2018)
In diabetes, compromised glucose utilization leads the heart to use FA almost exclusively for ATP generation. Chronically, this adaptation unfortunately leads to the conversion of FA to potentially toxic FA metabolites. Paired with increased formation of reactive oxygen species related to excessive mitochondrial oxidation of FA, can provoke cardiac cell death. To protect against this cell demise, intrinsic mechanisms must be available to the heart. Vascular endothelial growth factor B (VEGFB) may be one growth factor that plays an important role in protecting against heart failure. As a member of the VEGF family, initial studies with VEGFB focused on its role in angiogenesis. Surprisingly, VEGFB does not appear to play a direct role in angiogenesis under normal conditions or even when overexpressed, but has been implicated in influencing vascular growth indirectly by affecting VEGFA action. Intriguingly, VEGFB has also been shown to alter gene expression of proteins involved in cardiac metabolism and promote cell survival. Conversely, multiple models of heart failure, including diabetic cardiomyopathy, have indicated a significant drop in VEGFB. In this review, we will discuss the biology of VEGFB, and its relationship to diabetic cardiomyopathy.